The Impact of Globalization and Migration on Regional Hadith Studies - Abdullah Arafah; Ammar Makarim; Neni Nurlaela; Dadah (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the impact of globalization and migration patterns on the development of regional Hadith studies in the context of the contemporary Muslim world. As the second authoritative source in Islam, Hadith has undergone dynamic processes of transmission, interpretation, and adaptation that vary across different Muslim regions. Using a qualitative approach through literature review and comparative analysis, this research identifies three main patterns emerging as a result of globalization and migration: (1) methodological hybridization in Hadith studies that blends local traditions with transnational approaches; (2) the transformation of Hadith authority from a hierarchical-traditional model to a more complex global network; and (3) the recontextualization of Hadith to address specific socio-cultural challenges in various regions. The findings reveal that globalization and migration have facilitated the exchange of Hadith knowledge across regions, creating a new "geography of Hadith knowledge" that transcends traditional territorial boundaries. However, this study also highlights the tensions between universalizing and particularizing tendencies in regional Hadith studies, where efforts are made to preserve local cultural identities while adopting transnational methodologies. The implications of these findings underscore the need for a new analytical framework in Hadith studies that accommodates spatial-territorial dimensions and the dynamics of knowledge mobility in the global era.